Poly(N,N-Dimethylaminoethyl Methacrylate) for Removing Chromium (Vi) Through Polymer-Enhanced Ultrafiltration Technique - Sanchez-Poblete, J (Elsevier B.V., 2018)
This work is focused on the removal of Cr(VI) ions from aqueous solution using polymer-enhanced ultrafiltration (PEUF) techniques with water-soluble poly(N,N-dimethylaminoethyl methacrylate), PDMAEMA, used as sorbent. The polymer was prepared by reversible addition-fragmentation chain transfer (RAFT) polymerization at different reaction times, characterized by size exclusion chromatography (SEC) and proton nuclear magnetic resonance (1H NMR). The sorption of Cr(VI) was studied by PEUF as a function of pH, the polymer:Cr(VI) molar ratio, and the presence of interfering ions. The PEUF-enrichment mode was used to saturate the polymer and further determine the release of Cr(VI) and regeneration of the polymer using sorption-desorption process. The RAFT polymerization showed a yield in the range 46% to 79% (determined by 1H NMR) for polymers with molecular weight (Mn) between 28 and 195 kg mol−1. The polydispersity estimated by SEC was between 1.1 and 1.8. The capacity of PDMAEMA as sorbent of Cr(VI), by the PEUF technique showed an efficient removal of Cr(VI) (100%, 25 mg L−1 in the feed) at pH 4 using polymer:Cr molar ratio of 40:1. The presence of interfering ions does not significantly decrease the retention capacity of PDMAEMA. Finally the results indicated that PDMAEMA can release Cr(VI) and be regenerated. © 2018 Elsevier B.V.